Modified Cloze Test, Essay Test, Personal & Collaborative Writing Tasks in EFL Composition Class at Universitas Andalas - Hanafi Hanafi (Universitas PGRI Adi Buana Surabaya, 2023)
This retrospective study reports a quantitative analysis of two types of assignments and two test forms used to measure improvement of student’s writing skill in two composition classes at Universitas Andalas, West Sumatera, Indonesia. This project aims to identify the different roles of the two test forms used as well as the relationship and learning effects between the two test forms and weekly personal writing task or in-class group tasks. In this research, two EFL classes of Composition with two different groups of students in two successive academic years were observed. The classes’ activities, held through fourteen meetings for learning activities and two meetings for mid-term and end-of-term examinations, consisted of weekly assignments of composing paragraphs or short essays individually and collaboratively. The first composition class used an integrative test, i.e. cloze test, as the mid semester examination and a short essay test as the final semester examination. The second class used only essay test for both exams. The individual weekly writing task was assigned in both classes while the collaborative writing task was assigned only in the first class. The pearson r corelational analyses on scores of the assignments and the tests in both classes shows that the modified cloze test appeared to still correlately weakly with the essay test but, through t-test analyses, still significant in detecting the learning effect. Personal weekly writing assignments correlate strongly with essay test while the collaborative work appeared to have less significant learning effect on the student's writing competence.